Late-Onset Ornithine Transcarbamylase Deficiency and Variable Phenotypes in Vietnamese Females With OTC Mutations - Nguyen, Huy-Hoang; Khanh Nguyen, Ngoc; Dung Vu, Chi; Thu Huong Nguyen, Thi; Nguyen, Ngoc-Lan (Frontiers in Pediatrics, 2020)
Background: Ornithine transcarbamylase deficiency (OTCD) is an X- linked recessive disorder and the most common error of the urea cycle, caused by the mutations in the OTC gene. Due to X-inactivation, 15–20% of female carriers present symptoms of OTCD at late onset. Early diagnosis of OTCD by molecular analysis in females is highly desirable. The aim of the study was to identify the mutations in two unrelated Vietnamese girls suspected with OTCD and the carriers in their families for definitive diagnosis and proper counseling. Case Presentation: Two patients presented with an acute encephalopathy at the first admission. Biochemical tests revealed hyperammonemia, hyperlactatemia, elevated glutamine level, elevated transaminase, elevated urinary orotic and uracil acid levels, and disorder of prothrombin time. Brain magnetic resonance imaging indicated cerebral edema. Based on the clinical and laboratory results, the two patients were diagnosed with urea cycle disorders. Therefore, the two patients were managed by stopping feeding, with infused glucose, l-carnitine, l-arginine, and sodium benzoate, and with hemofiltration. The two patients were alert and recovered with normal blood ammonia levels after 72 h of treatment. The family history of patient 1 showed that her brother died at 4 days of age due to a coma and dyspnea, while her parents were asymptomatic. Variable phenotypes were observed in three generations of the patient 2's family, including asymptomatic (mother), affected female adults dying at the first symptom (grandmother and aunt), and affected males dying in the first week of life (uncle, cousin, and siblings). Whole-exome sequencing showed two mutations in the OTC gene, including one novel missense mutation, c.365A>T, in the patient 1 and one previously reported splicing mutation, c.717+1G>A, in the patient 2. The two mutations are evaluated as likely pathogenic and pathogenic, respectively, according to the recommendations of the American College of Medical Genetics and Genomics (ACMG). Genetic analyses in the families indicated the mothers were heterozygous. Conclusion: Clinical, biochemical, and molecular findings accurately diagnosed the two patients with late-onset OTCD. Our results explained the genetic causes and proposed the risk in the patients' families, which could be useful for genetic counseling and monitoring in prenatal diagnosis.